Cartilage: Biomimetic Study of the Extracellular Matrix. Issue 1622 (2014) - Anyaeji, Chinedu I.; Basser, Peter J.; Horkay, Ferenc
ABSTRACT: Cartilage is a complex biological tissue that exhibits gel-like behavior. Its primary biological function is providing compressive resistance to external loading and nearly frictionless lubrication of joints. In this study, we model cartilage extracellular matrix using a biomimetic system. We demonstrate that poly(vinyl) alcohol (PVA) hydrogels are robust biomaterials exhibiting mechanical and swelling properties similar to that of cartilage extracellular matrix. A comparison is made between the macroscopic behavior of PVA gels and literature data reported for cartilage.